Agroindustrial Firm's Financial Strategy during Pandemic: Case Study in PTPN X, Jember Regency - Maharani, Bunga; Aprillianto, Bayu; Budi Sulistiyo, Agung; Wulandari Widiyanti, Novi; Miqdad, Muhammad (KnE Social Sciences, 2024)
This qualitative research aimed to explore the financial policies and strategies adopted by companies in the agro-industrial sector in an effort to improve their financial performance, especially during the COVID-19 pandemic. The research used a case study approach conducted at PTPN X Jember. PTPN X Jember is an agro-industry company that produces world-class tobacco as its main product. Through in-depth interviews and periodic observations, data mining was carried out by considering one finance director as the main informant and supplemented by an in-depth review of financial report documents as secondary data reinforcement. Data analysis adopts Miles and Huberman’s technique consisting of three activities, i.e. data reduction, data display, and drawing conclusions/verification. The results of the study indicated that there is a strong preference for PTPN X to carry out a cost optimization strategy to encourage increased performance, which had an impact on increasing the quantity and quality of products. Quality products had a direct effect on increasing profits despite the COVID-19 pandemic situation. This research contributed to the development of financial management literature, especially corporate financial strategies during times of crisis in the agro-industrial sector. Keywords: agro-industry, financial performance, Human Resources, cost optimization strategy